The Right to Portuguese Nationality: B’nei anussim brazilians between the cross and the menorah - Paes de Barros, João Ernesto (Revista Jurídica Portucalense, 2015)
In february 2015 was issued a regulament for the descendent of the jews who were expelled in 1496, to obtain portuguese nationality. However, the most significant document to prove the legal condition is subject to a certification which will be issued by jewish communities whose trait is to not recognize members of branches other than orthodox as jewish. The objective of this research is to analyze this right and its repercussion to brazilian descendents of jews who do not follow the same faith of the jewish which makes such certifications.